Global, regional, and national burden of head and neck cancer in males and associated risk factors from 1990 to 2021: a systematic analysis for the Global Burden of Disease Study 2021 - Jiang, Junjie; Xia, Zhongfang; Yao, Wei (Frontiers in Oncology, 2025)
BackgroundHead and neck cancer (HNC) is one of the most prevalent malignant tumors, with higher incidence and mortality rates in men than in women, particularly for lip and oral cavity, nasopharyngeal, laryngeal, and other pharyngeal cancers. This study investigates global trends in the occurrence of these cancers in men from 1990 to 2021 and analyzes their changing trends to guide healthcare policymakers in resource allocation.MethodsUsing data from the 2021 Global Burden of Disease Study (GBD 2021), this study assesses the global prevalence, incidence, mortality, and disability-adjusted life years (DALYs) for male head and neck cancers. It also evaluates the relationship between cancer burden and economic development using the Socio-Demographic Index (SDI) and analyzes the risk factors for male head and neck cancer mortality and DALYs.ResultsFrom 1990 to 2021, the impact of male head and neck cancers increased at varying rates. In 2021, there were 968,573 prevalent cases of lip and oral cavity cancer, 272,917 incident cases, 136,890 deaths, and 3,969,812 DALYs globally. The burden of nasopharyngeal, laryngeal, and other pharyngeal cancers was lower, with 385,913, 939,924, and 258,723 prevalent cases, respectively. The age-standardized incidence rates for all four cancers were positively correlated with the SDI. Key risk factors for male head and neck cancers include smoking and alcohol consumption. Additional risk factors include chewing tobacco for lip and oral cavity cancer deaths, formaldehyde exposure for nasopharyngeal cancer, and occupational exposure to sulfuric acid and asbestos for laryngeal cancer.ConclusionsLip and oral cavity cancer remains the most burdensome, while nasopharyngeal cancer is increasing in East and Southeast Asia. Laryngeal cancer has declined in high-SDI regions, while other pharyngeal cancers are rising. Gender and lifestyle are key risk factors, underscoring the need for early prevention, particularly in resource-limited areas. As the global population ages, targeted prevention and improved healthcare infrastructure are essential.